2002
DOI: 10.2337/diacare.25.12.2238
|View full text |Cite
|
Sign up to set email alerts
|

Valuing Health-Related Quality of Life in Diabetes

Abstract: OBJECTIVE -Cost-utility analyses use information on health utilities to compare medical treatments that have different clinical outcomes and impacts on survival. The purpose of this study was to describe the health utilities associated with diabetes and its treatments, complications, and comorbidities.RESEARCH DESIGN AND METHODS -We studied 2,048 subjects with type 1 and type 2 diabetes recruited from specialty clinics at a university medical center. We administered a questionnaire to each individual to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
254
4
17

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 325 publications
(297 citation statements)
references
References 27 publications
22
254
4
17
Order By: Relevance
“…Our results are consistent with other studies that have demonstrated lower health-utility scores in women with diabetes [6,[31][32][33] and worse QoL in the presence of complications [6,20,33,34]. However, even with inclusion of gender and diabetic complications in the model, frequency of hyperglycemic symptoms was associated with lower health-utility scores.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are consistent with other studies that have demonstrated lower health-utility scores in women with diabetes [6,[31][32][33] and worse QoL in the presence of complications [6,20,33,34]. However, even with inclusion of gender and diabetic complications in the model, frequency of hyperglycemic symptoms was associated with lower health-utility scores.…”
Section: Discussionsupporting
confidence: 92%
“…Previously, we have shown that major diabetes complications are associated with lower healthutility scores [6]. Our current study involved four questions: first, which symptoms in the QWB-SA are most strongly associated with measures of glycemia (self-reported frequencies of symptomatic hyperglycemia and hypoglycemia, and HbA1c) in patients with diabetes?…”
Section: Introductionmentioning
confidence: 95%
“…The absolute decrement for amputation was converted into utility decrement factors that could be multiplied by the individual's current EQ-5D to estimate the relative effect of the complication. Utility decrements for renal failure and foot ulcers were not available from the UKPDS study described above, so were obtained from a different study 303 of 2048 subjects with type 1 diabetes mellitus and T2DM. Utility decrements for the variety of cardiovascular events were taken from a HTA assessing statins to reflect the utility decrements in the general population.…”
Section: Utility Decrementsmentioning
confidence: 99%
“…Seventh, we removed the costs for administrative charges from the base case and reduced the lost productivity hours associated with an OGTT to 2 h. Finally, we decreased the rate of progression of diabetes from 8 to 2% in order to reflect the lower rates of progression reported in predominantly white populations (6). We extrapolated the base case results to a cohort of 1,000 women and calculated incremental cost per case for annual, biannual, and every 3-year OGTT screening (23).…”
Section: Sensitivity Analysesmentioning
confidence: 99%